People Expectations to Social Welfare Provision by Government Agencies in Rayong Province - เวชสวรรค์, ภัทรา; รชตวัฒนกุล, สุวัจ; รชตวัฒนกุล, สนใจ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The study aims to investigate the expectations towards the social welfare provision by government agencies, using, Rayong Province as a case study. The objectives are to examine the level of expectations of the residents in Rayong Province towards the social welfare provision by government agencies and to compare the level of expectations of the residents in Rayong Province That Quantitative research methods. Sub-district towards the social welfare provision by government agencies, categorized by personal factors. The sample group for the study consists of 375 residents in Rayong Province,. Data collection tools include online questionnaires administered through simple random sampling. Statistical analysis methods used include: 1) calculating percentages, 2) finding means, 3) calculating standard deviations, and 4) hypothesis testing.          The study findings based on the objectives are as follows: 1) Investigation of the level of expectations of residents in Rayong Province That Sub-district towards the social welfare provision by government agencies revealed that the overall level of expectation is at the highest level. When considering specific aspects, it was found that the aspect with the highest average rating is healthcare welfare, followed by education welfare, residential welfare, general social service welfare, employment and income stability welfare, legal justice welfare, and the lowest average rating is recreational welfare, respectively. 2) Comparative study of the level of expectations of people in front of the Rayong Province regarding social welfare provision of government agencies. It was found that the expectations regarding social welfare provision of government agencies Public sector of people with different number of persons in families There is a difference in expectations regarding social welfare provision by government agencies, with statistical significance at the .05 level, in line with the set assumptions. and expectations regarding social welfare provision by government agencies of people of different genders, ages, statuses, educational levels, occupations, and monthly incomes. different There are expectations for social welfare provision by government agencies. no different The statistical significance level .05 does not meet the set assumptions.